2014
DOI: 10.1007/s00253-014-5778-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of salinity on the anaerobic metabolism of phosphate-accumulating organisms (PAO) and glycogen-accumulating organisms (GAO)

Abstract: The use of saline water as secondary quality water in urban environments for sanitation is a promising alternative towards mitigating fresh water scarcity. However, this alternative will increase the salinity in the wastewater generated that may affect the biological wastewater treatment processes, such as biological phosphorus removal. In addition to the production of saline wastewater by the direct use of saline water in urban environments, saline wastewater is also generated by some industries. Intrusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 30 publications
1
33
0
1
Order By: Relevance
“…Such a deviation might be originated from the relative large error of the percentage of Ca-polyP (Table 2), estimated by EDX analysis. Notably, the PAO metabolic shift from PAM to GAM was also observed as the salinity of the system was elevated to a certain level (Welles et al, 2014). In our study, as the influent calcium concentration was increased from 15 to 96 mg/L, the salinity changed slightly.…”
Section: Mechanism For the Change Of Pao Metabolic Pathwaymentioning
confidence: 54%
See 1 more Smart Citation
“…Such a deviation might be originated from the relative large error of the percentage of Ca-polyP (Table 2), estimated by EDX analysis. Notably, the PAO metabolic shift from PAM to GAM was also observed as the salinity of the system was elevated to a certain level (Welles et al, 2014). In our study, as the influent calcium concentration was increased from 15 to 96 mg/L, the salinity changed slightly.…”
Section: Mechanism For the Change Of Pao Metabolic Pathwaymentioning
confidence: 54%
“…PAOs may tune their metabolic pathway to partially use GAO metabolism under certain conditions (Erdal et al, 2008;Barat et al, 2006Barat et al, , 2008Zhou et al, 2008;Acevedo et al, 2012;Welles et al, 2014). The metabolic pathway of PAOs could be shifted between the dominance of PAM and GAM along with the change of intracellular polyP level, which was confirmed by the evolution of PHA and glycogen in EBPR systems (Acevedo et al, 2012).…”
Section: Introductionmentioning
confidence: 83%
“…The influent of SBR-S contained a 75%-to-25% mixture of acetate-to-propionate: 280 mg HAc/L (9.5 C-mmol/L, 300 mg COD/L, 645 mg NaAc$3H 2 O) and 67 mg/L HPr (2.72 C-mmol/L, 100 mg COD/L, 6.675 Â 10 À2 mL C 3 H 6 O 2 ), leading to an influent P/C ratio of 0.066 (P-mol/C-mol). Further details regarding other macronutrients and trace elements can be found elsewhere (Smolders et al, 1994;Welles et al, 2014).…”
Section: Synthetic Mediummentioning
confidence: 99%
“…The differences in operational factors between the SBR are listed in Table 1. Further details regarding the operational conditions of SBR-L, SBR-S and SBR-W can be found elsewhere (Welles et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bassin et al [41] reported that at high salinity levels (33.0 g/L NaCl), GAOs gained advantage over PAOs in their long-term experiment. Welles et al [42] conducted a short-term experiment and also suggested that salinity higher than 6.0 g/L of NaCl favored GAOs over PAOs. Thus, the activity of PAOs in this system was almost not observed.…”
Section: Effect Of Salinity On Phosphorus Removalmentioning
confidence: 99%